Enhancing Mobile Learning Platforms through Meaningful Gamification: Heatmaps, Quizzes, and Time-Based Rewards - Lamsal, Krishna; Bhattarai, Sudhan; Pokharel, Sulav; Baral, Sashank; Shrestha, Sushil; Dahal, Niroj; Hasan, Md. Kamrul (International Journal of Interactive Mobile Technologies (iJIM), 2025)
Developing long-term study habits through gamification in educational platforms presents a significant challenge. The approaches taken by modern gamified platforms and researchers to gamify the educational platform often rely on extrinsic rewards akin to video games, which engage students but fail to cultivate the intrinsic motivation necessary for habit development. Educational platforms commonly implement badges, leaderboards, achievements, and points (BLAP) that predominantly reward students for their results rather than their effort, thereby lacking meaningful gamification. To address these issues, this paper proposes alternative strategies such as competitive player-vs-player quizzes, visual time statistics, and a habit-tracking heatmap to foster intrinsic motivation through a competitive environment that enhances self-awareness and cultivates a growth mindset. This research utilized an initial survey and literature review to identify the shortcomings of existing gamification approaches, developed a prototype based on the hypotheses, and engaged participants in interactive sessions to gather qualitative feedback. Subsequently, a quantitative survey measured the effectiveness of the proposed strategies. As an initial exploratory study, this paper aims to lay the groundwork for future empirical validation of these strategies. The findings from this phase provide initial validation that these new features may serve as effective alternatives to traditional gamification elements. While the study suggests these methods have potential, a longitudinal evaluation is necessary to assess their long-term impact on study habits.